The Palgrave Handbook of Populism
XXVIII, 700 p. 20 illus., 6 illus. in color.
Keywords: This handbook assesses the phenomenon of populism – a concept frequently belabored, but often misunderstood in politics. Rising populism presents one of the great challenges for liberal democracies, but despite the large body of research, the larger picture remains elusive. This volume seeks to understand the causes and workings of modern-day populism, and plumb the depths of the fears and frustrations of people who have forsaken established parties. Although the main focus of this volume is political science, there are more disciplines represented in order to get a whole picture of the debate. It is comprised of strong empirical and theoretical papers that also bear social relevance. Michael Oswald is Assistant Professor of Politics at the University of Passau, Germany, and the author of Mobilization, Representation, and Responsiveness in the American Democracy (Palgrave Macmillan, 2020).